Association between the c. 2495 A>G ATP7B Polymorphism and Sporadic Alzheimer's Disease. (22nd May 2011) - Bucossi, Serena; Mariani, Stefania; Ventriglia, Mariacarla; Polimanti, Renato; Gennarelli, Massimo; Bonvicini, Cristian; Pasqualetti, Patrizio; Scrascia, Federica; Migliore, Simone; Vernieri, Fabrizio; Rossini, Paolo M.; Squitti, Rosanna
Abstract : Nonceruloplasmin-bound copper ("free") is reported to be elevated in Alzheimer's disease (AD). In Wilson's disease (WD) Cu-ATPase 7B protein tightly controls free copper body levels. To explore whether the ATP7B gene harbours susceptibility loci for AD, we screened 180 AD chromosomes for sequence changes in exons 2, 5, 8, 10, 14, and 16, where most of the Mediterranean WD-causing mutations lie. No WD mutation, but sequence changes corresponding to c.1216 T>G Single-Nucleotide Polymorphism (SNP) and c.2495 A>G SNP were found. Thereafter, we genotyped 190 AD patients and 164 controls for these SNPs frequencies estimation. Logistic regression analyses revealed either a trend for the c.1216 SNP (P = .074 ) or a higher frequency for c.2495 SNP of the GG genotype in patients, increasing the probability of AD by 74% (P = .028 ). Presence of the GG genotype in ATP7B c.2495 could account for copper dysfunction in AD which has been shown to raise the probability of the disease.